Strobe training as a visual training method that improves performance in climbing - Vasile, Antonia Ioana; Stănescu, Monica Iulia (Frontiers in Sports and Active Living, 2024)
Introduction Strobe training is a form of visual training where the athlete has to practice during intermittently dark conditions. Strobe training improves visual, perceptual, and cognitive skills, which will enhance athletic performance. Strobe training can influence multiple training components in climbing: psychological, tactical, physical, and technical training. Materials and methods The study was conducted on 17 elite climbers from Romania (10 male and 7 female), representing the entire National Youth Climbing Team. The research group was divided into a control group (n = 8) and an experimental group (n = 9). The used instruments were the Cognitrom battery (for cognitive skills, such as spatial skills and reactivity), the Witty SEM system (for motor-cognitive skills, such as cognitive agility, visual processing speed, and visual memory), and the International Rock Climbing Research Association (IRCRA) performance-related test battery for climbers (climbing-specific motor skills). The experimental group had 20 strobe training sessions, which took place during one calendar year, as an additional session to their climbing schedule done with their principal trainer. The strobe session was once a week, depending on the periodization of the macrocycle (preparatory, competitional, and transition periods). The control group and the experimental group had similar climbing training sessions during the 1-year macrocycle in terms of intensity and volume of their training. Results Strobe training improved on-sight performance (d = 0.38) and red-point performance (d = 0.36). Strobe training improved the majority of cognitive skills [all spatial skills (d = 1.27 for mental image transformation; d = 1.14 for spatial orientation; d = 1.59 for image generation) and simple reaction time (d = 0.99)]. Strobe training improved all motor-cognitive skills (d = 0.16 for visual memory; d = 1.96 for visual memory errors; d = 1.39 for visual processing speed; d = 1.94 for visual processing errors; d = 1.30 for cognitive agility). Strobe training improved many climbing-specific parameters (flexibility and upper body strength) (d = 0.44 and d = 0.47 for flexibility parameters; d = 0.50 to 0.73 for upper body strength parameters). Discussion Strobe training is an effective training method for enhancing performance that should be used on more experienced climbers. It acts more on spatial skills, rather than on reactivity skills, developing the visual-motor coordination system. Strobe training has greater effects on climbers aged below 16 years, as youth athletes rely more on visual input compared to adults. The improvement in climbing-specific variables was due to the additional climbing session done weekly. Strobe training acts more on the cognitive component of training than on the motor component of training in climbing.